TLR4 increases the stemness and is highly expressed in relapsed human hepatocellular carcinoma. (8th April 2019) - Zhou, Shuang; Du, Renle; Wang, Zhenglu; Shen, Wenzhi; Gao, Ruifang; Jiang, Shan; Fang, Yan; Shi, Yuzhi; Chang, Antao; Liu, Lei; Liu, Chenghu; Li, Na; et al.
Abstract: Toll‐like receptor 4 (TLR4) plays an essential role in cancer progress. Here, we find that the expression of TLR4 in relapsed human hepatocellular carcinoma (HCC) clinical samples is higher than that in the non‐relapsed ones, which leads us to explore the role of TLR4 in cancer stemness. We reported that TLR4‐AKT signaling pathway was activated by lipopolysaccharides (LPS) in HCC cell lines to enhance the cancer stemness capacity, which was reflected by the increased percentage of CD133 + CD49f + population and side population, enhanced sphere formation, and the upregulation of stemness marker gene‐ SOX2 . Downregulation of SOX2 attenuated the enhanced HCC stemness induced by LPS, indicating SOX2 as a downstream mediator of LPS‐TLR4 signaling. The role of LPS‐TLR4 signaling in inducing HCC stemness was further confirmed by tumor xenograft experiment in vivo. Taken together, our findings provide a novel therapeutic target to prevent the recurrence of HCC. Abstract : We find that the expressions of TLR4 and SOX2 in relapsed hepatocellular carcinoma (HCC) clinical samples are higher than those in the unrelapsed ones. We report that TLR4‐AKT signaling pathway is activated by lipopolysaccharides (LPS) to enhance the stemness capacity of HCC.